2018
DOI: 10.1002/cm.21447
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of β tubulin isotypes with glutathione in differentiated neuroblastoma cells subject to oxidative stress

Abstract: Microtubules are a major component of the neuronal cytoskeleton. Tubulin, the subunit protein of microtubules, is an α/β heterodimer. Both α and β exist as families of isotypes, whose members are encoded by different genes and have different amino acid sequences. The βII and βIII isotypes are very prominent in the nervous system. Our previous work has suggested that βII may play a role in neuronal differentiation, but the role of βIII in neurons is not well understood. In the work reported here, we examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…β-tubulin was chosen as the loading control based on a previously published study [ 114 ] which showed that the treatment of neuroblastoma cells with high concentrations of BSO (5 mM, or 12.5 mM) for 24 h affected the actin cytoskeletal network but not β-tubulin. Although β-tubulin has been shown by some studies to interact with GSH and form GSH-tubulin mixed disulfides, this interaction has been shown to occur at high (i) temperatures (30 °C) [ 115 ]; (ii) concentrations of GSH (∼5 mM) [ 116 ]; and (iii) levels of steady-state ROS [ 116 ]. The concentration and duration of treatment for PAO and DTT were selected from previous studies in literature where they were shown to be non-toxic [ 57 , 117 , 118 ].…”
Section: Resultsmentioning
confidence: 99%
“…β-tubulin was chosen as the loading control based on a previously published study [ 114 ] which showed that the treatment of neuroblastoma cells with high concentrations of BSO (5 mM, or 12.5 mM) for 24 h affected the actin cytoskeletal network but not β-tubulin. Although β-tubulin has been shown by some studies to interact with GSH and form GSH-tubulin mixed disulfides, this interaction has been shown to occur at high (i) temperatures (30 °C) [ 115 ]; (ii) concentrations of GSH (∼5 mM) [ 116 ]; and (iii) levels of steady-state ROS [ 116 ]. The concentration and duration of treatment for PAO and DTT were selected from previous studies in literature where they were shown to be non-toxic [ 57 , 117 , 118 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since virtually no cell expresses only a single isotype of tubulin, one can probably assume that cellular microtubules rich in βIII are highly dynamic. Fourth, βIII responds to oxidative stress by binding to glutathione, much more so than do either βI or βII ( Guo et al, 2018 ). Finally, different approaches have shown that the presence of βIII protects the cell from oxidative or other stresses ( Gan et al, 2007 ; Guo et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…The first set, called “HMBG βIII,” is based on the sequences of βIII from humans ( H omo) , mice ( M us ), cows ( B os ), and chickens ( G allus ). βIII-Tubulin from each of these is identical at the positions of interest and are, in a sense, being privileged because they may be the only organisms in which the functional properties of their βIII has been examined ( Lopata and Cleveland, 1987 ; Banerjee et al, 1992 ; Panda et al, 1994 ; Joe et al, 2008 ; Guo et al, 2010 , 2011 , 2018 ; Vemu et al, 2016 ). The second set, called “Vert βIII” refers to the 8 residues that appear to be conserved in all vertebrate βIII-tubulins, as described above.…”
Section: Dissecting the βIii-tubulin Isotype And Its Roles In Neuronsmentioning
confidence: 99%
“…Hcy in high concentrations acts as an oxidant due to its interaction with the heme proteins of the cell [ 39 , 40 ]. S-homocysteinylation could occur when Hcy directly reacts with β-3-tubulin cysteine residues, mimicking glutathione [ 41 ]. Furthermore, Chen et al have demonstrated that proteins in hela cell lysates undergo unspecific N-homocysteinylation of lysine residues, and that TUBB3 is among them [ 42 ].…”
Section: Discussionmentioning
confidence: 99%